Identifikasi Ruang Komunal pada Permukiman Padat Penduduk - Sherly Defannya Serdani; Verry Damayanti (UNISBA Press, 2023)
Abstract. Cicadas Subdistrict is one of the densely populated in the center of Bandung City. One of the RW's is a TNI AD housing complex with limited access. Limited land causes this area to not have sufficient communal space as a means of community interaction. The purpose of this research is to identify communal spaces in dense settlements in Cicadas Subdistrict. This study uses an empirical and spatial approach that is used to get an overview of current conditions in identifying communal spaces in densely populated settlements in Cicadas Subdistrict. The analysis in this study uses empirical quantitative analysis to determine the location of communal and spatial spaces by mapping the distribution of communal spaces using ArcGIS software. To obtain data, a primary survey and a secondary survey were carried out, from the results of the identification of the distribution of communal spaces in Cicadas Subdistict, it is known that communal spaces in Cicadas Subdistict consist of 7 RW halls, 1 Buruan Sae, 13 street points/alleys, 1 subdistrict office, 4 fields, 1 madrasah, 11 mosques, 3 security posts, 2 posts, 3 posyandu, 1 resident's house, 2 parks, and 2 stalls spread across almost all RW's. The majority of these communal spaces are communal spaces that are not planned as communal spaces such as houses, alleys, fields and parks that are not functioning properly, especially places that are very close to residential areas with informal activities and a very frequent frequency. The limited land available also gives rise to unique communal spaces, such as